2008
DOI: 10.1088/0957-4484/19/37/375201
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of exciton photodissociation, charge transport and photovoltaic response of poly(N-vinyl carbazole):TiO2nanocomposites for solar cell applications

Abstract: The photogeneration of charge carriers in spin-coated thin films of nanocrystalline (nc-)TiO(2) particles dispersed in a semiconducting polymer, poly(N-vinylcarbazole) (PVK), has been studied by photoluminescence and charge transport measurements. The solvent and the TiO(2) particle concentration have been selected to optimize the composite morphology. A large number of small domains leading to a large interface and an improved exciton dissociation could be obtained with tetrahydrofuran (THF). The charge trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…It has been demonstrated that there is often an interface activation energy barrier Φ B at the heterojunction. At present, the formation of the Φ B are usually explained as a result of the energy level bending by the vaccum level misalignments at the heterojunction or the formation of interface chargetransfer states, [11] and Φ B can be evaluated from the dark reverse saturation current in dark J-V characteristic by: [12,13] …”
Section: Characterizationmentioning
confidence: 99%
“…It has been demonstrated that there is often an interface activation energy barrier Φ B at the heterojunction. At present, the formation of the Φ B are usually explained as a result of the energy level bending by the vaccum level misalignments at the heterojunction or the formation of interface chargetransfer states, [11] and Φ B can be evaluated from the dark reverse saturation current in dark J-V characteristic by: [12,13] …”
Section: Characterizationmentioning
confidence: 99%
“…Organic solar cells have many advantages such as potential to be semi-transparent, manufacture on both large or small areas compatible with mass production and low-cost, production possibility with continuous coating and printing processes on lightweight and flexible substrates (for example textiles), ecological and low-temperature production possibilities (Dennler et al, 2006a;Dennler & Sariciftci, 2005). Polymer heterojunction organic solar cells have attracted much attention because of their potential applications in large area, flexible and low-cost devices (Park et al, 2009;Chang et al, 2009;Dridi et al, 2008;Peet et al, 2009;Oey et al, 2006;Yu et al, 2008). Polymer based thin films on flexible and non-flexible substrates can be achieved by various printing techniques (see Fig.…”
Section: Organic Solar Cellsmentioning
confidence: 99%
“…Recent reports have shown that PVK could be very useful as a host material in white-organic light-emitting diodes (WOLEDs) [29,41], in combination with other layers, because of its high energy blue-emissive singlet excited state and the absence of low energy triplet state [30]. Moreover, PVK has also been used in dye-sensitized solar cells blended with TiO 2 as the electron donor and hole-transporting material [31][32][33][34]42]. The interest has grown up recently because of new promising performances in PCs, FETs, and LEDs for carbazole derivatives and related polymers [35].…”
Section: Polycarbazolesmentioning
confidence: 99%